Danger signals in stroke and their role on microglia activation after ischemia - Gülke, Eileen; Gelderblom, Mathias; Magnus, Tim (Therapeutic advances in neurological disorders, 2018)
Ischemic stroke is a major cause of death. Besides the direct damage resulting from oxygen and glucose deprivation, sterile inflammation plays a pivotal role in increasing cellular death. Damaged-associated molecular patterns (DAMPs) are passively released from dying cells and activate the innate immune system. Thus, they take part in the direct and rapid activation of the inflammatory response after stroke onset. In this review the role of the most important DAMPs, high mobility group box 1, heat and cold shock proteins, purines, and peroxiredoxins, are addressed. Moreover, intracellular pathways activated by DAMPs in microglia are illuminated.